The association of parity number with multimorbidity and polypharmacy among Iranian women in the Azarcohort: a cross-sectional study - Elnaz Faramarzi; Mohammd Hossein Somi; Helda Tutunchi; Hanieh Almaspour; Sarvin Sanaie; Sanaz Asemani (BMC, 2023)
Abstract Objective We aimed to study the association of parity number with multimorbidity (MM) and polypharmacy among women in the Azar cohort population. Patients & methods This cross-sectional investigation was based on data from the Azar Cohort Study. Information regarding demographics, personal habits, physical activity level, medical and reproductive history, and anthropometric measurements of 8,290 females (35-70 years) were evaluated. Ordinal logistic and logistic regression analyses were conducted to assess for associations of parity number with multimorbidity (MM), polypharmacy, chronic disease, and abdominal obesity. Results More educated participants and people in the fifth quintile of the Wealth Score Index were less likely to have a higher parity number. With increasing parity numbers, the prevalence of MM, polypharmacy, hypertension, cardiovascular disease, fatty liver disease, stroke, rheumatoid diseases, chronic obstructive pulmonary disease, and cancers tended to rise. Moreover, we found that increasing parity numbers (especially when ≥ 5) enhanced the odds of abdominal obesity, waist-to-hip ratio ≥ 0.85, and waist-to-height ratio ≥ 0.5; these significant associations were more obvious in parity numbers ≥ 9 and WHtR ≥ 0.5. Conclusion The parity number is associated with MM and polypharmacy in Iranian women enrolled in the Azar Cohort Study. Further studies exploring the pathways (biological, social, and environmental) underlying these relationships will provide clues for preventing morbidity and premature mortality among susceptible andhighly parous women.